2018
DOI: 10.1186/s40413-018-0199-y
|View full text |Cite
|
Sign up to set email alerts
|

Allergy diagnosis from symptoms to molecules, or from molecules to symptoms: a comparative clinical study

Abstract: BackgroundClassical allergy diagnostic workup “from symptoms to molecules” comprises 1) clinical investigation, 2) skin prick- and IgE- testing, and recently, 3) molecular allergy testing. We aimed to examine the diagnostic fidelity of the alternative approach “from molecules to symptoms”, which was recently suggested in the EAACI Molecular Allergology User’s Guide, in a retrospective clinical study.MethodsRecords from 202 patients with clinically suspected allergic sensitizations were extracted from files at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Based on clinical history and results of the ISAC112, alder, birch, hazel, ash, grasses, mugwort, ragweed (ambrosia), buckhorn plantain, house dust mites, cat, dog, and Alternaria among airborne allergens and hazelnut, peanut, wheat flour, egg, cow milk, soy, and cod fish from nutritional allergens were tested in skin prick test as reported previously. 9 …”
Section: Methodsmentioning
confidence: 99%
“…Based on clinical history and results of the ISAC112, alder, birch, hazel, ash, grasses, mugwort, ragweed (ambrosia), buckhorn plantain, house dust mites, cat, dog, and Alternaria among airborne allergens and hazelnut, peanut, wheat flour, egg, cow milk, soy, and cod fish from nutritional allergens were tested in skin prick test as reported previously. 9 …”
Section: Methodsmentioning
confidence: 99%
“…5,74 It is accepted as a first-line diagnostic tool and helps to reduce the time to diagnosis, while having the same precision as the conservative SPT-first approach. 332 Overall, debate in the allergy community reveals that the initial skepticism regarding PAMD@ 121 has moved towards the possibility that it could replace SPT in the future. 122 The path forward for PAMD@ must include education regarding its clinical utility, how to interpret results to improve the identification of clinically relevant primary and cross-reactivity rather than cross-sensitization, and its costeffectiveness.…”
Section: Unmet Needsmentioning
confidence: 99%
“…80 A recent comparative clinical study has shown that the multiplex analysis of IgE to allergenic molecules is a reliable diagnostic tool, which also has proved to be time efficient by decreasing the number of performed SPTs. 81 Concerning the Identification of clinically relevant inhalant allergen sources (ie, tree, grass, or weed pollen) is required before allergenspecific immunotherapy.…”
Section: Diagnostic Use Of Molecules For Ait Prescription Comparing Omentioning
confidence: 99%